2015
DOI: 10.1111/jcmm.12535
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR‐93 as a suitable miR for normalizing miRNA in plasma of tuberculosis patients

Abstract: Tuberculosis (TB) remains a major public health issue. New tests to aid diagnoses and monitor the response to therapy are urgently required. There is growing interest in the use of microRNA (miRNA) profiles as diagnostic, prognostic or predictive markers in a range of clinical and infectious diseases, including Mycobacterium tuberculosis infection, however, challenges exist to accurately normalise miRNA levels in cohorts. This study examined the appropriateness of 12 miRs and RNU6B to normalise circulating pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Host microRNA-gene interactions during the infection response are also proving to be a fruitful source of potential diagnostic biomarkers for specific infections, as well as distinguishing between active and latent infections; for example, the use of such markers to discriminate between latent infection and active disease with M. tuberculosis 88 . As with the other diagnostic uses of small RNA biomarkers described in this Review, a number of hurdles exist for the development and validation of infection assays, including sensitivity, specificity and, perhaps more difficult to overcome, the normalization of small RNA in clinical samples, which will vary between conditions, tissues and individual hosts and is an active area of study 89 . However, the application of RNA-seq provides a useful orthogonal approach to genomics-based diagnostics for clinical microbiology.…”
Section: Companion Diagnosticmentioning
confidence: 99%
“…Host microRNA-gene interactions during the infection response are also proving to be a fruitful source of potential diagnostic biomarkers for specific infections, as well as distinguishing between active and latent infections; for example, the use of such markers to discriminate between latent infection and active disease with M. tuberculosis 88 . As with the other diagnostic uses of small RNA biomarkers described in this Review, a number of hurdles exist for the development and validation of infection assays, including sensitivity, specificity and, perhaps more difficult to overcome, the normalization of small RNA in clinical samples, which will vary between conditions, tissues and individual hosts and is an active area of study 89 . However, the application of RNA-seq provides a useful orthogonal approach to genomics-based diagnostics for clinical microbiology.…”
Section: Companion Diagnosticmentioning
confidence: 99%
“…Additionally, there are still many challenges in the accurate normalization of miRNA levels among different cohorts. Recent trials that normalized miRNA levels between cohorts from Australia and China identified only miR‐93 as the most suitable reference miRNA in both cohorts, with large variations in several miRNAs between the cohorts (Barry et al, ). Currently, several miRNAs, including miR‐223, miR‐144*, and miR‐29, may be associated with host responses against TB, but the value of these miRNAs as biomarkers for diagnostics has not been demonstrated.…”
Section: Mirna Profiling In Human Tbmentioning
confidence: 99%
“…Additionally, there are still many challenges in the accurate normalization of miRNA levels among different cohorts. Recent trials that normalized miRNA levels between cohorts from Australia and China identified only miR-93 as the most suitable reference miRNA in both cohorts, with large variations in several miRNAs between the cohorts (Barry et al, 2015).…”
Section: Mirna Profiling In Human Tbmentioning
confidence: 99%
“…Most of the results obtained by qPCR used different reference genes for normalization, such as miR-16, miR-93-5p in skeletal disease10121314. Although miR-93 had been defined as a plasma miRNA reference gene for tuberculosis17, it was also connected with osteoblast differentiation and bone mineralization18. External reference couldn’t correct for the other causes of variability such as the total concentration of miRNA fraction.…”
mentioning
confidence: 99%